Flexible thermal interface material and preparation method and application thereof

By using intrinsic self-healing silicone polymers, liquid metal microcapsules, and hydroxylated ceramic powders as thermal fillers in traditional silicone thermal interface materials, high-performance flexible thermal interface materials are prepared, which solves the problem of using traditional materials in the use of The problems of mechanical damage and insufficient thermal conductivity during the process have achieved self-repair and improved thermal conductivity of the material.

CN119431798APending Publication Date: 2025-02-14YUNNAN KEWEI LIQUID METAL VALLEY R & D CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411413892.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Traditional silicone thermal interface materials are easily damaged by mechanical fatigue or external forces after long-term use, which affects their durability and service life. At the same time, the thermal conductivity of thermal fillers is low, resulting in insufficient thermal conductivity.

Method used

The intrinsic self-healing silicone polymer is used as the matrix, and liquid metal microcapsules and hydroxylated ceramic powders are filled as thermal fillers. By preparing at a certain mass ratio, high-performance flexible thermal interface materials are prepared.

Benefits of technology

The material has excellent thermal conductivity, flexibility, elasticity and high compression. It can quickly repair itself after being crushed by external forces, significantly improving durability and service life, while maintaining lightweight, easy processing and chemical corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431798A_ABST
    Figure CN119431798A_ABST
Patent Text Reader

Abstract

The invention relates to the field of thermal interface materials, in particular to a flexible thermal interface material and a preparation method and application thereof. The flexible thermal interface material comprises an organic polymer material and a heat-conducting filler filled in the organic polymer material, wherein the organic polymer material comprises an intrinsic self-repairing organosilicon polymer, the heat-conducting filler comprises a liquid metal microcapsule and hydroxylated ceramic powder, and the mass ratio of the heat-conducting filler to the organic polymer material is (65: 35)-(95: 5). The high-performance flexible thermal interface material is prepared by filling the rigid ceramic and the flexible liquid metal into the self-repairing organic silicon polymer according to a certain ratio, has flexibility, elasticity, high compressibility and repairability, is suitable for various uneven concave-convex interfaces, and can be used as a thermal interface material after being crushed by external force. And self-repairing can be quickly carried out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of thermal interface materials, and in particular to a flexible thermal interface material and a preparation method thereof. Background Art

[0002] With the development and progress of science and technology, high-performance and high-reliability electronic products have become the development trend of future products, and the demand is constantly increasing, which has prompted the development of electronic devices towards higher integration, and the heat generated per unit area continues to rise. In order to meet the heat dissipation needs, the heat generated by electronic devices needs to be transferred to the heat sink through the thermal interface material, and then dissipated into the air by the heat sink. However, ordinary thermal conductive materials have poor resilience or no resilience. After long-term use, gaps will appear between the heat-generating components and the radiator.

[0003] Traditional silicone thermal interface materials use polydimethylsiloxane as the base polymer, add thermal conductive fillers with different thermal conductivities, and control the cross-linking degree of the base polymer to obtain a semi-solid material that is between soft and sticky. During use, it will be affected by its own internal fatigue or external effects, resulting in microscopic or macroscopic mechanical damage, which in turn affects the durability and service life of the material or electronic device. In addition, the thermal conductive fillers of traditional silicone thermal interface materials are mainly rigid inorganic powder materials, such as boron nitride (BN), aluminum nitride (AlN), silicon nitride (Si3N4), aluminum oxide (Al2O3), zinc oxide (ZnO), silicon carbide (SiC), etc., and their thermal conductivity is lower than that of metal and carbon-based materials. Therefore, the thermal conductivity of traditional silicone thermal interface materials mainly depends on the filling amount of fillers. The addition of high filling amount will reduce the mechanical properties of the thermal conductive gasket, and it is very easy to be deformed and broken by external forces during use, and the thermal conductivity will decline. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a flexible thermal interface material and a preparation method and application thereof.

[0005] In the first aspect, the flexible thermal interface material provided by the present invention comprises: an organic polymer material, and a thermally conductive filler filled in the organic polymer material; wherein the organic polymer material comprises an intrinsic self-healing silicone polymer, the thermally conductive filler comprises liquid metal microcapsules and hydroxylated ceramic powder, and the mass ratio of the thermally conductive filler to the organic polymer material is 65:35~95:5. The present invention prepares a high-performance flexible thermal interface material by filling rigid ceramic and flexible liquid metal double fillers into an intrinsic self-healing silicone polymer in proportion. The material has excellent thermal conductivity, and at the same time has significant flexibility, elasticity and high compression performance, and can better adapt to various uneven interfaces. After being crushed by external force, the material can quickly self-repair, which significantly improves its durability and service life. The material also has the characteristics of light weight, easy processing, excellent mechanical properties, chemical corrosion resistance, puncture resistance and insulation, and can meet the needs of a variety of complex application environments.

[0006] According to the present invention, the traditional silicone thermal interface material is composed of silicone polymer and inorganic thermal conductive filler. The huge thermal resistance between the thermal conductive particles determines that the thermal conductivity of the traditional silicone thermal pad is poor, and the rigid inorganic filler is filled into the silicone polymer. During use, it will be affected by its own internal fatigue or external effects, thereby causing microscopic or macroscopic mechanical damage, thereby affecting the durability and service life of the material or electronic device. The present invention provides a high-performance flexible thermal interface material, which is composed of an intrinsic self-repairing silicone polymer and a thermal conductive filler (liquid metal microcapsule and hydroxylated ceramic powder). The intrinsic self-repairing silicone polymer can self-repair after mechanical damage to restore its structural and functional integrity. The flexible and elastic properties enable this material to cover various uneven surfaces well, providing efficient thermal conductivity and reliable mechanical stability. The liquid metal microcapsules and hydroxylated ceramic powders used in the present invention are used as thermal conductive fillers, and are filled into the intrinsic self-repairing silicone polymer in a certain mass ratio to obtain a high-performance flexible thermal interface material. This material not only has excellent thermal conductivity, but also has significant flexibility, elasticity and high compressibility, and can adapt to various uneven interfaces. Moreover, after being crushed by external forces, the material can quickly self-repair, which improves the durability and service life of the material, while maintaining its light weight, easy processing, excellent mechanical properties and chemical corrosion resistance, and has anti-puncture and insulation functions.

[0007] Preferably, the mass ratio of the thermal conductive filler to the organic polymer material is 70:30 to 90:10. Rigid ceramic and flexible liquid metal dual fillers are used and filled into the self-healing silicone polymer in a certain ratio to obtain a high-performance flexible thermal interface material. The material has excellent flexibility, elasticity, high compressibility and repairability, is suitable for various uneven concave-convex interfaces, and can quickly self-repair after being crushed by external force.

[0008] Preferably, the mass ratio of the liquid metal microcapsules to the hydroxylated ceramic powder is 1-10:1-10.

[0009] More preferably, the mass ratio of the liquid metal microcapsules to the hydroxylated ceramic powder is 1-2:1-2.

[0010] In the present invention, the flexible thermal interface material adopts rigid ceramic and flexible liquid metal dual fillers, which are filled into the self-healing silicone polymer in a certain ratio, and the self-healing is better completed in combination with the effect of the intrinsic self-healing silicone polymer. The obtained high-performance flexible thermal interface material has better flexibility, elasticity, high compressibility and repairability, can be better applied to various uneven concave and convex interfaces, and can quickly perform self-repair after being crushed by external force.

[0011] Further preferably, the ceramic powder in the hydroxylated ceramic powder is selected from one or more of aluminum powder, boron nitride (BN), aluminum nitride (AlN), silicon nitride (Si3N4), aluminum oxide (Al2O3), zinc oxide (ZnO), and silicon carbide (SiC), and more preferably aluminum oxide. The hydroxylated ceramic powder is obtained by surface modification of ceramic powder; preferably, the ceramic powder is hydroxylated and subjected to high temperature treatment to obtain the hydroxylated ceramic powder.

[0012] Preferably, the raw materials of the organic polymer material include a first monomer and / or a second monomer. In the present invention, the first monomer and the second monomer undergo addition reaction to generate an organic polymer containing one or both of dynamic non-covalent chemical bonds and dynamic covalent chemical bonds, ensuring that the polymer synthesized from the formulated monomers has repairability.

[0013] Preferably, the first monomer is prepared from raw materials including octamethylcyclotetrasiloxane, (3-aminopropyl)methylbisethoxysilane, hexamethyldisiloxane and deionized water; and the second monomer is formylbenzoic acid.

[0014] More preferably, the mass ratio of octamethylcyclotetrasiloxane, (3-aminopropyl)methylbisethoxysilane, hexamethyldisiloxane and deionized water is 100-300:50-400:0.5-5:10-100, preferably 200:150-300:1.2-2.5:30-50.

[0015] Further preferably, the mass ratio of the first monomer to the second monomer is 2-5:1, preferably 3.5-4:1, such as 3.65:1, 3.70:1, 3.75:1, 3.76:1, 3.77:1, 3.85:1, etc. and any numerical range therebetween. By using the preferred monomers and ratios, the self-healing silicone polymer-based flexible thermal interface material has high thermal conductivity, excellent flexibility and elasticity, high compressibility and self-healing ability, which can effectively improve the heat dissipation efficiency and service life of the device in the application.

[0016] Preferably, the liquid metal microcapsule comprises a low melting point metal and a polydopamine coating layer, and the low melting point metal is encapsulated in the polydopamine coating layer.

[0017] Preferably, the mass ratio of the low melting point metal to the polydopamine coating layer is 5~60:1.5~8, and the low melting point metal is a low melting point alloy or non-eutectic material with a melting point below 70°C; the low melting point metal is preferably selected from one or more of gallium, gallium indium, gallium indium tin, gallium indium zinc, gallium indium tin zinc bismuth, bismuth indium tin, and bismuth indium tin zinc. In the present invention, the liquid metal microcapsules are formed by high-frequency ultrasonic dispersion of low melting point metal in dopamine hydrochloride solution, and dopamine hydrochloride self-polymerizes on the surface of liquid metal microdroplets under an alkaline environment to form a polydopamine coating layer, and the low melting point metal droplets are encapsulated into the PDA shell to improve the problem of long-term oxidation of low melting point metal droplets. And due to the high light-to-heat conversion of PDA, PDA wrapped in low melting point metal droplets will deform under infrared light irradiation, fully filling the gaps in the thermal interface material to form a complete thermal conductive path.

[0018] In a second aspect, the present invention provides a method for preparing the flexible thermal interface material, comprising: 1) Mixing raw materials including liquid metal microcapsules, hydroxylated ceramic powder and organic polymer material monomers to obtain a thermal interface material precursor; 2) vulcanizing and pressing the thermal interface material precursor.

[0019] The polymer-based flexible thermal interface material provided by the present invention uses liquid metal and ceramic powder as thermal conductive fillers, wherein the liquid metal is processed to form liquid metal microcapsules, and the ceramic powder is surface-modified to form hydroxylated ceramic powder. The liquid metal microcapsules and hydroxylated ceramic powder are filled into an intrinsic self-healing organic silicon polymer in a certain ratio to obtain a high-performance flexible thermal interface material.

[0020] Preferably, step 1) further comprises ultrasonically dispersing the low melting point metal to obtain liquid metal droplets, mixing the liquid metal droplets with a dopamine hydrochloride solution and subjecting the mixture to self-polymerization to obtain liquid metal microcapsules; the ultrasonic dispersion is performed at a temperature of 60-70°C, a frequency of 25000-35000 Hz, and a time of 3-8 min.

[0021] Preferably, step 1) further comprises subjecting the ceramic powder to hydroxylation treatment, wherein the ceramic powder and the hydroxy compound are ball-milled and mixed, and then annealed at a temperature of 950-1100° C. to obtain hydroxylated ceramic powder; the hydroxy compound is preferably glycerol.

[0022] Further preferably, the aqueous solution of the hydroxyl compound is placed in a ball mill and ground and mixed with the ceramic powder for 20 to 40 minutes, preferably 30 minutes, so that the hydroxyl compound is evenly adhered to the surface of the ceramic powder, and then the treated ceramic powder is placed at a constant temperature of 950 to 1100° C., preferably 1000° C. for 0.8 to 1.2 hours, preferably 1 hour, to decompose the hydroxyl groups to obtain hydroxylated modified ceramic powder.

[0023] Preferably, step 1) further comprises mixing octamethylcyclotetrasiloxane, (3-aminopropyl)methylbisethoxysilane, hexamethyldisiloxane and deionized water, and then catalytically reacting in the presence of tetramethylammonium hydroxide, the reaction temperature is 85-95°C, the time is 5-7h, and then vacuum treatment is performed at 140-160°C. The self-healing silicone polymer-based flexible thermal interface material prepared by the method provided by the present invention has high thermal conductivity, excellent flexibility, elasticity and high compressibility, self-healing ability and significant durability, and greatly improves the heat dissipation efficiency and service life. The intrinsic self-healing silicone polymer used can complete self-healing well. The polymer-based flexible thermal conductive pad prepared by the present invention can be used to cover very uneven surfaces due to its flexibility and elasticity. The material can self-repair the damage and restore its structural integrity and functional integrity after being mechanically damaged by external force. During use, after being crushed by pressure, when the heating device is heated, it will self-repair and reunite the broken parts, restore its structural integrity and functional integrity, effectively improve the heat dissipation efficiency of the device, and extend its service life.

[0024] More preferably, step 1) further comprises treating the raw materials at 23-35° C. after mixing.

[0025] More preferably, in step 2), the vulcanization temperature is 75-85° C. and the time is 5-7 hours.

[0026] Further preferably, in step 2), the pressing includes subjecting the vulcanized material to a roller pressing process, preferably to 0.06-0.1 mm. The use of preferred vulcanization and pressing process conditions can effectively improve the mechanical properties, self-healing ability and thermal stability of the material, and can also significantly enhance thermal conductivity and durability.

[0027] In a third aspect, the present invention provides a flexible thermal interface material obtained by the above-mentioned preparation method or the use of the above-mentioned flexible thermal interface material as a self-repairing flexible thermal conductive pad in a heating device.

[0028] The beneficial effects of the present invention are at least as follows: the present invention adopts rigid ceramics and flexible liquid metal microcapsules as dual fillers, and fills them into a silicone polymer with self-healing properties in a certain ratio to obtain a high-performance flexible thermal interface material, which has excellent flexibility, elasticity, high compressibility and repairability, and is suitable for various uneven concave and convex interfaces, and can quickly self-repair after being crushed by external force. During use, after being crushed by pressure, when the heating device is heated, it will self-repair and reunite the broken parts, restore its structural integrity and functional integrity, effectively improve the heat dissipation efficiency of the device, and extend its service life. In addition, the liquid metal microcapsules will deform and fill the pores after being heated, forming a more complete heat conduction path with better thermal conductivity. At the same time, the use of ceramic fillers and the preparation of liquid metal microcapsules can further separate the liquid metal droplets, which can overcome the problem of leakage caused by the aggregation of liquid metal droplets, and make a more stable new liquid metal thermal interface material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 A flow chart for preparing a self-healing polymer-based flexible thermal interface material with dual fillers of liquid metal microcapsules and ceramic powders provided in an embodiment of the present invention.

[0031] Figure 2 Actual picture of the self-repairing process of the liquid metal microcapsule and ceramic powder dual filler self-repairing polymer-based flexible thermal interface material provided in an embodiment of the present invention.

[0032] Figure 3 SEM images of the self-healing material of the liquid metal microcapsule and ceramic powder dual filler self-healing polymer-based flexible thermal interface material provided in the embodiment of the present invention before and after repair. a is the cross-sectional view after cutting; b is the cross-sectional view after repair. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] It should be understood that the following examples are only exemplary illustrations and explanations of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect. Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available products, or can be prepared by known methods. If the specific technology or conditions are not specified in the examples, they are all conventional methods or carried out according to the technology or conditions described in the literature of the field, or according to the product instructions. The reagents and instruments used, etc., which do not indicate the manufacturer, are all conventional products that can be purchased through regular channels.

[0035] Example 1

[0036] This embodiment provides a liquid metal microcapsule and ceramic powder dual filler self-repairing polymer-based flexible thermal interface material, such as Figure 1 As shown, the preparation method thereof comprises: 1. Take 50g of liquid metal (melting point is 60℃), add it to 150mL of dopamine hydrochloride aqueous solution, ultrasonically disperse it at 65℃ and 3000Hz for 5min, stir it at room temperature for 40min, add Tris base to adjust the pH value to 8.5, continue to react for 3h, filter it, wash the filter residue with deionized water for 3 times to remove excess dopamine hydrochloride, and then dry it in a constant temperature oven at 50℃ for 24h to obtain liquid metal microcapsules.

[0037] 2. Place 50g of Al2O3 powder and 100g of hydroxyl compound in a ball mill and grind them thoroughly with grinding beads for 30 minutes, wherein the hydroxyl compound is a 10±2% glycerol aqueous solution. Then the powder is decomposed at 1000℃ for 1h to remove excess hydroxyl compound, thus obtaining a modified ceramic powder.

[0038] 3. Add 100 g of octamethylcyclotetrasiloxane, 115.2 g of (3-aminopropyl)methylbisethoxysilane and 1.1 g of hexamethyldisiloxane into a three-necked flask filled with 25 g of deionized water. Place the three-necked flask in an oil bath at 90°C, add tetramethylammonium hydroxide pentahydrate to catalyze the reaction for 6 hours, and then react in vacuum at 150°C to remove the catalyst and small molecules to obtain monomer 1.

[0039] 4. Take 7.9g of monomer 1 and add it into tetrahydrofuran to fully dissolve it to obtain solution 1. Take 20g of liquid metal microcapsules and 20g of modified ceramic powder and add them into solution 1 and stir them thoroughly. Then add tetrahydrofuran solution dissolved with 2.1g of formylbenzoic acid (monomer 2). After stirring thoroughly, remove the excess tetrahydrofuran solution on the upper layer. Remove the solvent from the lower layer of viscous material at a constant temperature of 25°C to obtain a thermal interface material precursor.

[0040] 5. The thermal interface material precursor is vulcanized in an oven at 80°C for 6 hours and then taken out, and then repeatedly rolled with a roller to a certain thickness to obtain a liquid metal microcapsule and ceramic powder dual filler self-healing polymer-based flexible thermal interface material with a certain thickness.

[0041] Figure 2 The self-repairing process of the liquid metal microcapsule and ceramic powder dual filler self-repairing polymer-based flexible thermal interface material provided in this embodiment is as follows: Figure 2 As shown, after the flexible thermal interface material prepared by the present invention is cut with a blade having a thickness of 0.5 μm, the interface begins to be repaired by adhesion after being kept at 80° C. for 10 minutes, and all the cut positions are repaired by adhesion after being kept at 80° C. for 30 minutes. Figure 3 The SEM images of the self-healing material of the liquid metal microcapsule and ceramic powder dual filler self-healing polymer-based flexible thermal interface material provided in the embodiment before and after repair (a is a cross-sectional view after cutting; b is a cross-sectional view after repair), as shown in FIG. Figure 3 As shown, the fracture distance at the damaged part using a 0.5μm thick blade is 142μm under an electron microscope. This is because the resilience of the flexible thermal interface material causes the fracture distance to be smaller than the thickness of the blade. After repair, the fracture distance disappears, and liquid metal droplets gather at the damaged part to form a new heat conduction path.

[0042] Example 2

[0043] This embodiment provides a liquid metal microcapsule and ceramic powder dual filler self-repairing polymer-based flexible thermal interface material, and the preparation method thereof includes: 1. Take 50g of liquid metal (melting point is 60℃), add it to 150mL of dopamine hydrochloride aqueous solution, ultrasonically disperse it at 65℃ and 30000Hz for 5min, stir it at room temperature for 40min, add Tris base to adjust the pH value to 8.5, continue to react for 3h, filter it, wash the filter residue with deionized water for 3 times to remove excess dopamine hydrochloride, and then dry it in a 50℃ oven at a constant temperature for 24h to obtain liquid metal microcapsules.

[0044] 2. Place 50g of Al2O3 powder and 100g of hydroxyl compound in a ball mill and grind them thoroughly with grinding beads for 30 minutes, wherein the hydroxyl compound is a 10±2% glycerol aqueous solution. Then the powder is decomposed at 1000℃ for 1h to remove excess hydroxyl compound, thus obtaining a modified ceramic powder.

[0045] 3. Add 100 g of octamethylcyclotetrasiloxane, 115.2 g of (3-aminopropyl)methylbisethoxysilane and 1.1 g of hexamethyldisiloxane into a three-necked flask filled with 25 g of deionized water. Place the three-necked flask in an oil bath at 90°C, add tetramethylammonium hydroxide pentahydrate to catalyze the reaction for 6 hours, and then react in vacuum at 150°C to remove the catalyst and small molecules to obtain monomer 1.

[0046] 4. Take 3.51g of monomer 1 and add it into tetrahydrofuran to fully dissolve it to obtain solution 1. Take 20g of liquid metal microcapsules and 20g of modified ceramic powder and add them into solution 1 and stir them thoroughly. Then add tetrahydrofuran solution dissolved with 0.93g of formylbenzoic acid (monomer 2). After stirring thoroughly, remove the excess tetrahydrofuran solution on the upper layer. Remove the solvent from the lower layer of viscous material at a constant temperature of 25°C to obtain a thermal interface material precursor.

[0047] 5. The thermal interface material precursor is vulcanized in an oven at 80°C for 6 hours and then taken out, and then repeatedly rolled with a roller to a certain thickness to obtain a liquid metal microcapsule and ceramic powder dual filler self-healing polymer-based flexible thermal interface material with a certain thickness.

[0048] Example 3

[0049] This embodiment provides a liquid metal microcapsule and ceramic powder dual filler self-repairing polymer-based flexible thermal interface material, and the preparation method thereof includes: 1. Take 50g of liquid metal (melting point is 60℃), add it to 150mL of dopamine hydrochloride aqueous solution, ultrasonically disperse it at 65℃ and 30000Hz for 5min, stir it at room temperature for 40min, add Tris base to adjust the pH value to 8.5, continue to react for 3h, filter it, wash the filter residue with deionized water for 3 times to remove excess dopamine hydrochloride, and then dry it in a 50℃ oven at a constant temperature for 24h to obtain liquid metal microcapsules.

[0050] 2. Place 50g of Al2O3 powder and 100g of hydroxyl compound in a ball mill and grind them thoroughly with grinding beads for 30 minutes, wherein the hydroxyl compound is a 10±2% glycerol aqueous solution. Then the powder is decomposed at 1000℃ for 1h to remove excess hydroxyl compound, thus obtaining a modified ceramic powder.

[0051] 3. Add 100 g of octamethylcyclotetrasiloxane, 115.2 g of (3-aminopropyl)methylbisethoxysilane and 1.1 g of hexamethyldisiloxane into a three-necked flask filled with 25 g of deionized water. Place the three-necked flask in an oil bath at 90°C, add tetramethylammonium hydroxide pentahydrate to catalyze the reaction for 6 hours, and then react in vacuum at 150°C to remove the catalyst and small molecules to obtain monomer 1.

[0052] 4. Take 13.5g of monomer 1 and add it into tetrahydrofuran to fully dissolve it to obtain solution 1. Take 20g of liquid metal microcapsules and 20g of modified ceramic powder and add them into solution 1 and stir them thoroughly. Then add tetrahydrofuran solution containing 3.6g of formylbenzoic acid (monomer 2). After stirring thoroughly, remove the excess tetrahydrofuran solution on the upper layer. Remove the solvent from the lower layer of viscous material at a constant temperature of 25°C to obtain a thermal interface material precursor.

[0053] 5. The thermal interface material precursor is taken out, and then repeatedly rolled by a pressure roller to a certain thickness to obtain a liquid metal microcapsule and ceramic powder dual filler self-healing polymer-based flexible thermal interface material with a certain thickness.

[0054] Example 4

[0055] This embodiment provides a liquid metal microcapsule and ceramic powder dual filler self-repairing polymer-based flexible thermal interface material, and the preparation method thereof includes: 1. Take 50g of liquid metal (melting point is 60℃), add it to 150mL of dopamine hydrochloride aqueous solution, ultrasonically disperse it at 65℃ and 30000Hz for 5min, stir it at room temperature for 40min, add Tris base to adjust the pH value to 8.5, continue to react for 3h, filter it, wash the filter residue with deionized water for 3 times to remove excess dopamine hydrochloride, and then dry it in a 50℃ oven at a constant temperature for 24h to obtain liquid metal microcapsules.

[0056] 2. Place 50g of Al2O3 powder and 100g of hydroxyl compound in a ball mill and grind them thoroughly with grinding beads for 30 minutes, wherein the hydroxyl compound is a 10±2% glycerol aqueous solution. Then the powder is decomposed at 1000℃ for 1h to remove excess hydroxyl compound, thus obtaining a modified ceramic powder.

[0057] 3. Take 20g of liquid metal microcapsules and 20g of modified ceramic powder, stir them thoroughly, add 6g of double-end vinyl silicone oil and 4g of hydrogen-containing silicone oil, stir them thoroughly, pour them into a mold, and vulcanize them in an oven at 80°C for 6h to obtain a thermal interface material. This embodiment does not contain a dynamic repair bond, and the matrix cannot be repaired after being damaged.

[0058] Comparative Example 1

[0059] The same method as in Example 1 is used, except that the liquid metal is not wrapped with polydopamine. The preparation method includes: 1. Take 50g of liquid metal (melting point is 60℃), add it to 150mL of aqueous solution, disperse it ultrasonically at 65℃ and 3000Hz for 5min, stir it at room temperature for 40min, and filter it to obtain liquid metal droplets.

[0060] 2. Place 50g of Al2O3 powder and 100g of hydroxyl compound in a ball mill and grind them thoroughly with grinding beads for 30 minutes, wherein the hydroxyl compound is an 8% to 12% glycerol aqueous solution. Then the powder is decomposed at 1000℃ for 1h to remove excess hydroxyl compound, thus obtaining a modified ceramic powder.

[0061] 3. Add 100 g of octamethylcyclotetrasiloxane, 115.2 g of (3-aminopropyl)methylbisethoxysilane and 1.1 g of hexamethyldisiloxane into a three-necked flask filled with 25 g of deionized water. Place the three-necked flask in an oil bath at 90°C, add tetramethylammonium hydroxide pentahydrate to catalyze the reaction for 6 hours, and then react in vacuum at 150°C to remove the catalyst and small molecules to obtain monomer 1.

[0062] 4. Take 7.9g of monomer 1 and add it into tetrahydrofuran to fully dissolve it to obtain solution 1. Take 20g of liquid metal microcapsules and 20g of modified ceramic powder and add them into solution 1 and stir them thoroughly. Then add tetrahydrofuran solution dissolved with 2.1g of formylbenzoic acid (monomer 2). After stirring thoroughly, remove the excess tetrahydrofuran solution on the upper layer. Remove the solvent from the lower layer of viscous material at a constant temperature of 25°C to obtain a thermal interface material precursor.

[0063] 5. The thermal interface material precursor is vulcanized in an oven at 80°C for 6 hours and then taken out, and then repeatedly rolled with a roller to a certain thickness to obtain a liquid metal microcapsule and ceramic powder dual filler self-healing polymer-based flexible thermal interface material with a certain thickness.

[0064] Comparative Example 2

[0065] The same method as in Example 1 is used, except that Al2O3 is not subjected to hydroxylation treatment. The preparation method includes: 1. Take 50g of liquid metal (melting point is 60℃), add it to 150mL of dopamine hydrochloride aqueous solution, ultrasonically disperse it at 65℃ and 30000Hz for 5min, stir it at room temperature for 40min, add Tris base to adjust the pH value to 8.5, continue to react for 3h, filter it, wash the filter residue with deionized water for 3 times to remove excess dopamine hydrochloride, and then dry it in a 50℃ oven at a constant temperature for 24h to obtain liquid metal microcapsules.

[0066] 2. Add 100 g of octamethylcyclotetrasiloxane, 115.2 g of (3-aminopropyl)methylbisethoxysilane and 1.1 g of hexamethyldisiloxane into a three-necked flask filled with 25 g of deionized water. Place the three-necked flask in an oil bath at 90°C, add tetramethylammonium hydroxide pentahydrate to catalyze the reaction for 6 hours, and then react in vacuum at 150°C to remove the catalyst and small molecules to obtain monomer 1.

[0067] 3. Take 7.9g of monomer 1 and add it into tetrahydrofuran to fully dissolve it to obtain solution 1. Take 20g of liquid metal microcapsules and 20g of Al2O3 powder and add them into solution 1 and stir them thoroughly. Then add tetrahydrofuran solution containing 2.1g of formylbenzoic acid (monomer 2). After stirring thoroughly, remove the excess tetrahydrofuran solution on the upper layer. Remove the solvent from the lower layer of viscous material at a constant temperature of 25°C to obtain a thermal interface material precursor.

[0068] 5. The thermal interface material precursor is vulcanized in an oven at 80°C for 6 hours and then taken out, and then repeatedly rolled with a roller to a certain thickness to obtain a liquid metal microcapsule and ceramic powder dual filler self-healing polymer-based flexible thermal interface material with a certain thickness.

[0069] The performance tests of the composite phase change materials prepared in the above embodiments and comparative examples were conducted using the following methods: 1. Thermal resistance test: refer to ASTM D5470 standard test; 2. Thermal conductivity test: refer to GB / T 32064-2015 standard test; the test results are as follows.

[0070] Table 1

[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A flexible thermal interface material, characterized in that: include: An organic polymer material, and a thermally conductive filler filled in the organic polymer material; wherein the organic polymer material comprises an intrinsic self-healing silicone polymer, the thermally conductive filler comprises liquid metal microcapsules and hydroxylated ceramic powder, and the mass ratio of the thermally conductive filler to the organic polymer material is 65:35~95:

5.

2. The flexible thermal interface material according to claim 1, characterized in that: The mass ratio of the thermal conductive filler to the organic polymer material is 70:30-90:

10.

3. The flexible thermal interface material according to claim 2, characterized in that: The mass ratio of the liquid metal microcapsules to the hydroxylated ceramic powder is 1-10:1-10.

4. The flexible thermal interface material according to any one of claims 1 to 3, characterized in that: The ceramic powder in the hydroxylated ceramic powder is selected from one or more of aluminum powder, boron nitride, aluminum nitride, silicon nitride, aluminum oxide, zinc oxide, and silicon carbide.

5. The flexible thermal interface material according to any one of claims 1 to 4, characterized in that: The raw material of the organic polymer material includes a first monomer and / or a second monomer; Preferably, the first monomer is prepared from raw materials including octamethylcyclotetrasiloxane, (3-aminopropyl)methylbisethoxysilane, hexamethyldisiloxane and deionized water; and the second monomer is formylbenzoic acid.

6. The flexible thermal interface material according to any one of claims 1 to 5, characterized in that: The liquid metal microcapsule comprises a low melting point metal and a polydopamine coating layer, wherein the low melting point metal is encapsulated in the polydopamine coating layer; Preferably, the low melting point metal is a low melting point alloy or non-eutectic material with a melting point below 70°C; the low melting point metal is preferably selected from one or more of gallium, gallium indium, gallium indium tin, gallium indium zinc, gallium indium tin zinc bismuth, bismuth indium tin, and bismuth indium tin zinc.

7. The method for preparing the flexible thermal interface material according to any one of claims 1 to 6, characterized in that: include: 1) Mixing raw materials including liquid metal microcapsules, hydroxylated ceramic powder and organic polymer material monomers to obtain a thermal interface material precursor; 2) vulcanizing and pressing the thermal interface material precursor.

8. The method for preparing the flexible thermal interface material according to claim 7, characterized in that: Step 1) further comprises ultrasonically dispersing the low melting point metal to obtain liquid metal droplets, mixing the liquid metal droplets with a dopamine hydrochloride solution and self-polymerizing to obtain liquid metal microcapsules; the ultrasonic dispersion temperature is 60-70° C., the frequency is 25000-35000 Hz, and the time is 3-8 min; And / or, in step 1), the ceramic powder is further subjected to hydroxylation treatment, wherein the ceramic powder and the hydroxy compound are ball-milled and mixed, and then annealed at a temperature of 950-1100° C. to obtain hydroxylated ceramic powder; the hydroxy compound is preferably glycerol; And / or, in step 1), octamethylcyclotetrasiloxane, (3-aminopropyl)methylbisethoxysilane, hexamethyldisiloxane and deionized water are mixed, and then catalyzed in the presence of tetramethylammonium hydroxide.

9. The method for preparing the flexible thermal interface material according to claim 7 or 8, characterized in that: In step 1), the raw materials are mixed and then treated at 23-35°C; And / or, in step 2), the vulcanization temperature is 75-85°C; And / or, in step 2), the pressing includes subjecting the vulcanized material to a roller press.

10. Use of the flexible thermal interface material obtained by the preparation method according to any one of claims 1 to 6 or the flexible thermal interface material according to any one of claims 7 to 9 as a self-repairing flexible thermal conductive pad in a heat-generating device.